The impact of using AI tools in enhancing the analytical skills of mass communication students: a quasi-experimental study - Elgammal, Naglaa; Fawzy, Hala Elalfy; Elballat, Basma Abd_Elhay; Braimoh, Jimoh; Mosad, Asmaa (Frontiers in Education, 2026)
This study seeks to understand the effects of using artificial intelligence (AI) tools by mass communication students in developing their analytical skills of media content through a quasi-experimental study. The students were trained to use several AI tools, notably YouTube Scripter, Reader GPT, and NoteGPT, to extract written transcripts from videos, to use ChatGPT to discuss and analyze the written transcript or text, and to use GPT to read and interpret the video directly. Most of previous related studies focused on the use of AI tools in education from the descriptive perspective of attitudes or general applications. These studies lacked empirical investigation of the effects of the use of AI tools on the development of analytical skills specifically among mass communication students. Therefore, the present quasi-experimental study sets out to address this research gap by evaluating the impact of AI tools on the improvement of analytical skills among mass communication students at “October 6” University in Egypt. The fieldwork, conducted in December 2024, deployed a questionnaire using the time series method. A group of fourth-year students at the “October 6 University” in Egypt constituted the informants or subjects. Subsequently, the differences in the students’ responses, before and after using the AI tools to analyze the content of two news bulletins aired on DW and BBC channels, were measured. The results showed that using AI tools enhanced the students’ ability to analyze media content. The study recommended further research on leveraging AI tools in mass communication university education to enhance the students’ analytical skills for various types of media content, for example, the persuasive media content, and to equip media students with various skills that will make them suitable for optimal professionalism after graduation from the media school.